Effects of Flavolac Top Dress on Sow Body Weight and Litter Performance - Rafe Q. Royall; Karley R. Stephens; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Jordan T. Gebhardt; Robert D. Goodband; Analia M. Ribeiro da Silva; Kyle F. Coble (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 271 mixed-parity sows (PIC 1050) were used to evaluate the effect of feeding Flavolac in lactation diets on sow farrowing performance and litter growth performance during summer conditions. Flavolac (Agroceres Multimix; Rio Claro, Sao Paulo, Brazil) is a commercial product containing several compounds, including AAs, antioxidants, botanicals, direct fed-microbials, and vitamin-like compounds that have been shown to improve litter weaning weight or preweaning mortality in previous research. The experiment was conducted at a commercial sow farm located in northwest Texas. A total of four rooms (288 stalls; 144 stalls per treatment) were used. At approximately d 112 to 114 of gestation, sows were moved to the farrowing house and randomly allotted to one of two treatments based on parity and caliper score. Treatments consisted of a control (no Flavolac) or the control with an added Flavolac top-dress (80 g/d in a single feeding). Sows were weighed before entering the farrowing house and at weaning. Sows were provided approximately 4 lb per day of a common lactation diet without Flavolac pre-farrowing. After farrowing, sows were provided ad libitum access to lactation feed. The weaning age averaged approximately 21.3 d. There was no evidence of difference (P > 0.10) in sow at entry, weaning, or overall BW change. There was no evidence of differences (P > 0.10) for sow entry caliper, weaning caliper score, caliper score change, or average daily lactation feed disappearance. In addition, there was no evidence of difference (P > 0.10) in total litter, or piglet birth BW. However, administration of Flavolac tended (P < 0.10) to increase litter weaning weight, total litter weight gain, and litter average daily gain. Moreover, inclusion of Flavolac led to a tendency (P = 0.091) for a reduction in pre-weaning mortality and therefore an improvement in percentage of pigs weaned. In summary, the inclusion of Flavolac during the lactation period resulted in a tendency for reduced pre-weaning mortality and tended to improve total litter weight gain, and thus weight at weaning.
Keywords: feed additive; lactation; litter performance; sow